Loss of Hoxa5 function affects Hox gene expression in different biological contexts - Béatrice Frenette; Josselin Guéno; Nicolas Houde; Kim Landry-Truchon; Anthony Giguère; Theyjasvi Ashok; Abigail Ryckman; Brian R. Morton; Jennifer H. Mansfield; Lucie Jeannotte (Scientific Reports)
Abstract Hoxa5 plays numerous roles in development, but its downstream molecular effects are mostly unknown. We applied bulk RNA-seq assays to characterize the transcriptional impact of the loss of Hoxa5 gene function in seven different biological contexts, including developing respiratory and musculoskeletal tissues that present phenotypes in Hoxa5 mouse mutants. This global analysis revealed few common transcriptional changes, suggesting that HOXA5 acts mainly via the regulation of context-specific effectors. However, Hox genes themselves appeared as potentially conserved targets of HOXA5 across tissues. Notably, a trend toward reduced expression of HoxA genes was observed in Hoxa5 null mutants in several tissue contexts. Comparative analysis of epigenetic marks along the HoxA cluster in lung tissue from two different Hoxa5 mutant mouse lines revealed limited effect of either mutation indicating that Hoxa5 gene targeting did not significantly perturb the chromatin landscape of the surrounding HoxA cluster. Combined with the shared impact of the two Hoxa5 mutant alleles on phenotype and Hox expression, these data argue against the contribution of local cis effects to Hoxa5 mutant phenotypes and support the notion that the HOXA5 protein acts in trans in the control of Hox gene expression.